PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN SKINCARE SECARA ONLINE PADA MASA PANDEMI COVID-19 DI LINGKUNGAN MAHASISWI UNIVERSITAS NEGERI SURABAYA - Thoriq Septian Firjatullah; Ludvia Valentina Nor Febrianti; Savega Novialdi Pratama Putri; Dwi Heny Mutiara Laurina Wainggai; Fadhil Sahar Aqmar Nurcahyo (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
Indonesia is one of the countries affected by the Covid-19 pandemic. So that it has an impact on the community and students cannot meet directly on campus or in public places. Busyness as a student causes serious problems on facial skin, one of which is making the face dull and prone to breakouts. This is what encourages many students to do facial treatments using skincare. Facial care using skincare that is safe, reliable and affordable by students because it is affected by the pandemic which requires people to reduce activities outside the home, so many of them buy skincare online. This study aims to determine the effect of price on online skincare purchasing decisions during the pandemic. The object of this research is female students at the State University of Surabaya. The variables used are the influence of price and online skincare purchasing decisions. This study aims to analyze the effect of price on online skincare purchasing decisions during the COVID-19 pandemic in the female students of the State University of Surabaya.